2015
DOI: 10.1186/s13033-015-0033-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and associated factors among prisoners in North West Ethiopia: cross-sectional study

Abstract: BackgroundCurrently, mental health is an important public health problem and the leading cause of disability worldwide. Studies have shown that, mental illnesses are more common among the prison population than the general population. However, still there is no accurate count of persons with mental disorder who are incarcerated in Ethiopia and information about prisoners’ health conditions is scarce. The purpose of this study was to assess the prevalence and associated factors of psychological distress among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 7 , 17 , 18 , 31 ]. The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 1 , 21 , 22 , 31 , 32 , 33 ]. Some studies have reported that exposure to SHS in stressful states for a long time is related to the risk for negative lifestyle and behavioral problems such as emotional and conduct disorders at a young age [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 7 , 17 , 18 , 31 ]. The positive association between SHS exposure and mental health may be explained as integrating biological and epidemiological aspects [ 1 , 21 , 22 , 31 , 32 , 33 ]. Some studies have reported that exposure to SHS in stressful states for a long time is related to the risk for negative lifestyle and behavioral problems such as emotional and conduct disorders at a young age [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were several possible explanations about the relationship between exposure to passive smoke and mental distress among adult never-smokers in north-east China. Some research studies have reported that individuals who are in stressful state for a long time may have a variety of psychological problems, 25 26 and a positive lifestyle (incorporating physical exercise and healthy eating habits) was proved to be linked with a low risk of mental distress. 27 28 A previous study also demonstrated that Chinese traditional Confucianism may affect people not to express their feelings directly or take measures to change the unpleasant environment.…”
Section: Discussionmentioning
confidence: 99%
“…18% prevalence of co-morbid physical illness (comorbid illness indicated by PULSES)Medium*Beyen et al 2017 [88]PrevalencePrisonEthiopiaNRandom, YYes, Yes649, 27.8, 89.8%NANSGAD-7 (S), K10 (S), PHQ-9, (S) OSS (S), questionnaire (S)83.4% psychological distress (K10); 43.8% signs of depression (PHQ-9); 36.1% anxiety (GAD-7); 45.1% without social support (OSS). 17% suicidal ideation; 16.6% already planned to commit suicide; 11.9% at least one suicide attempt while in prison (questionnaire)Low*Dachew et al 2015 [89] (same sample as Beyen)PrevalencePrisonEthiopiaNRandom, YYes, Yes649, 27.8, 89.8%NANSK10 (S), questionnaire (S), MSPSS (S)83.4% psychological distress (K10). 43.6% of the respondents feel that they had been discriminated by their families, friends and significant others because of their imprisonment (questionnaire or MPSS, source not stated).…”
Section: Methodsmentioning
confidence: 99%